Behaviour of voids in a shear field - Tvergaard, Viggo (International journal of fracture, 2009)
When voids are present in a ductile material subject to a shear dominated stress state under low stress triaxiality the voids collapse to micro-cracks, which subsequently rotate and elongate in the shear field. In the present plane strain analyses for cylindrical voids a surface load normal to a plane connecting the ends of the micro-crack is used as an approximate representation of contact stresses during frictionless sliding. In a previous study of the same problem the author applied hydrostatic pressure inside the nearly closed micro-crack to approximate contact conditions. The transverse surface loads used in the present analyses avoid the tendency to unrealistically elongate the voids. It is found that even though the model applied here gives significantly later occurrence of a maximum overall shear stress than that found by using hydrostatic pressure, the present model does predict a maximum in all the cases analyzed and thus illustrates the micro-mechanism leading to failure of the material by localization of plastic flow.